Evaluation of Dominant Modes of Failure of Soil Nail System - Willon , Paul Nanak (Universiti Teknologi Petronas, 2009)
This report basically discusses the study and analyses conducted on the chosen project topic, which is Evaluation of Dominant Modes of Failure of Soil Nail System. The objective of the project is to quantify the non-quantitative factors that affecting failure of soil nail system to means of quantitative justification. Firstly, a comprehensive study on the soil nail system background such as the application, construction sequence, design methods, design requirements, materials used, etc are essential to get more understanding on the subject. Identification of uncertainties surround in soil nail system are necessary as the currently applied design methods are based on factor of safety which profoundly based on experience without regard to the degree of uncertainty. For that, hazard and risk related to uncertainties encircle in the soil nail system are identified through possible pre-failing failure mechanisms. Failure mechanisms consists of nail pullout failure, nail tendon failure, face failure and overall failure is identified through the failure modes analysis. Fault Tree Analysis (FTA) is applied to the failure mechanisms and the precedence events of each failure mechanism are determined. Four levels of AHP hierarchy model is constructed which consists of the overall goal / objective, criteria, sub-criteria and alternatives. Factors which have been determined in FTA are applied as the criteria and sub-criteria while failure mechanisms as the alternatives. The objective of the analysis is to determine the most probable failure mechanism in soil nail system. The final result of the AHP is in the forms numerical priority value for each failure mechanism. The overall consistency and sensitivity of overall judgments given is checked at the end of the analysis